Impact of microphone and receiver-in-the ear hearing aid technology on localization ability in hearing aid users - M C Chaithra; P. Manjula (The Egyptian Journal of Otolaryngology)
Abstract Background Individuals with sensorineural hearing loss often have poor localization abilities, and while hearing aids have been developed to address this, results vary. The current study aims to explore the benefits of hearing aids with microphone and receiver-in-the-ear (M&RIE) technology, which places the microphone in the ear canal along with two microphones of the regular receiver-in-the-ear hearing aid. In this study, a within-subject research design was conducted on 15 hearing aid users. The spatial localization ability was assessed using hearing aids with M&RIE and standard receivers. White noise was presented in an 18-loudspeaker setup, which was placed in a circle at 20° azimuths apart. Accuracy, RMS error, and spatial hemifield errors were computed. Result Significantly better performance was found in localization ability with hearing aids with M&RIE receiver compared to standard receiver. Participants with hearing aids with M&RIE receiver had lower overall mean RMS error (p < 0.001) and better accuracy scores (p < 0.001) in identifying sound sources in a 360° acoustic space compared to standard receivers. Front-back errors were significantly lower with M&RIE receiver. Conclusions It can be construed from the results that M&RIE technology in hearing aids offer significant advantages in addressing spatial deficits experienced by individuals with SNHL, preserving the pinna cues.